HUKUM PERBANKAN SYARIAH DI INDONESIA: Optimalisasi Fungsi Berbasis Pengendalian Risiko Pada Perbankan Syariah - Rahmawati; Muh Asad Imaduddin; Jufrin; Muslimah (STAI Syubbanul Wathon Magelang, 2023)
After Law Number 21 of 2008, the government attempted to increase the resilience of sharia banking to potential risks that could occur at any time. The systemic impact resulting from failure to control risk is the main reason for implementing strict regulations in the banking industry. the impact caused by the failure to control risks, and the implementation of strict regulations on the banking industry, and looking at the government's actions in forming regulatory rules regarding sharia banking. Considering this research, we look at the rules made by the government. Why is the main reason for implementing strict regulations in the banking industry. The aim of this research is to determine the impact of failure to control risk by sharia banking, and the implementation of strict regulations in the banking industry. This research uses a descriptive-qualitative approach, with a type of library research, namely a type of research by collecting scientific papers as research objects or collecting data in the nature of a library study. The research results show that the Government needs to improve the regulatory and supervisory function of sharia banking in Indonesia. To optimize the function of sharia banking, the government must be able to control the risks that always frame sharia banking business activities.